PVCbase: an integrated web resource for the PVC bacterial proteomes - Bordin, Nicola; González Sánchez, Juan Carlos; Devos, Damien (Database, 2018)
Interest in the Planctomycetes-Verrucomicrobia-Chlamydiae(PVC) bacterial superphy-lum is growing within the microbiology community. These organisms do not have a specialized web resource that gathersin silicopredictions in an integrated fashion. Hence, we are providing the PVC community with PVCbase, a specialized web resource that gathers in silico predictions in an integrated fashion. PVCbase integrates protein function annotations obtained through sequence analysis and tertiary structure prediction for 39 representative PVC proteomes (PVCdb), a protein feature visualizer (Foundation) and acustom BLAST webserver (PVCBlast) that allows to retrieve the annotation of a hit directly from the DataTables. We display results from various predictors, encompassingmost functional aspects, allowing users to have a more comprehensive overview of protein identities. Additionally, we illustrate how the application of PVCdb can be used to address biological questions from raw data.
Gesehen am 02.04.2020